Field notes and Hawk watch report contributed by Beth Proescholdt, fall 1996 - Proescholdt, Bethet al (1996)
Fall report of a Hawk watch at Grammer Grove County Wildlife Area contributed by Beth Proescholdt during the period from September 11 through December 1, 1996. Included with the Hawk watch is a field report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed/flatbed